Cooking Curries for change: four desi food blogs in the UK, cyberactivism, & the transnational public sphere. Issue 1 (2nd January 2020) - Gupta, Sukanya
ABSTRACT: This paper focuses on four popular UK based, desi food blogs by Anjali Pathak, Hari Ghotra, Mallika Basu, and Chintal Kakaya, who are ambassadors of the global justice charity Find Your Feet's (FYF) 'Curry for Change' (CFC) campaign. Reconfiguring and challenging geographical parameters and national boundaries, the bloggers team up with FYF to help fight hunger in African and Asian rural communities. Using the Internet as a platform to create awareness about the charity, the blogs share recipes and meal plans for dinner parties hosted in honour of the charity and invite the public to fundraising events. Concerned with human rights, these bloggers affect social change by empowering individuals and communities to participate in civic engagement, and occasionally to even challenge unfair government policies/practices. The blogs' efficacy can also be measured through the funds raised, the public attention they receive from channels such as Indian food network and London Live, local/regional newspapers such as the London Evening Standard, and magazines like India's Complete Wellbeing Magazine . Food blogs that actively contribute to global justice movements cannot be seen as domestic reflections or exercises in nostalgia anymore. Referring to Habermas's notion of the public sphere and Nancy Fraser's concept of the transnational public sphere, I examine these food blogs as transnational public spheres. Based on textual analysis of blog entries related specifically to the CFC campaign and an examination of FYF's annual reviews, this paper examines how these food blogs have expanded in form and function by engaging in cyberactivism.